Removal of macronutrients in the avocado fruit cv. Hass in Antioquia and Caldas, Colombia (2023)
In recent years, Colombia have become globally as one the major producer of Hass avocado. Contributions of all nutrients are made in the fertilization plans, but it is not known if the additions made have been adequate and opportune. Thus, the objective of this study was to determine the effects of site and year of productions on the removal of nutrients during the harvest stage of different tissues of the Avocado fruit cv. Hass in two farms (El-Sinaí and La-Escondida) located in the high-Andean tropical zone of Colombia in three years of production (2018-2020). For this purpose, fruit samples were taken at the harvest stage of highly productive trees from two sites in Colombia (i) El-Sinaí (Anserma, Caldas; altitude 2,000 m, average annual temperature and precipitation 18.65°C and 1,837 mm) and (ii) La-Escondida (Rionegro, Antioquia; altitude 2,200 m, average annual temperature and precipitation 16.84°C and 2,091 mm). The fruit tissues (peel, pulp, seed-coat and seed) were subjected to elemental composition analysis. Significant (P<0.05) differences were detected for each element between tissues, years, sites and their interactions. The total removal range for macronutrients was: N 1.53-2.57, P 0.21-0.38, K 2.53-3.51, Ca 0.20-0.56, Mg 0.15-0.24 and S 0.13-0.18 (kg t-1). These results indicate that the order of nutrient accumulation in the fruit was K > N > Ca > P >Mg > S and they may be used as a reference for elaboration of fertilization programs in the regions studied, particularly in terms of the doses and ratios of nutrients. Also, the nutrient concentration in the different fruit tissues may be used as a reference of fruit nutritional status of productive trees for farmers interested in monitoring and improving nutritional of low-yield trees.